Static and Dynamic Stereochemistry of Chiral Ln DOTA Analogues - Di Bari, Lorenzo; Salvadori, Piero (Chemphyschem, 2011)
Ln DOTA derivatives (DOTA=1,4,7,10‐tetraazacyclododecane‐1,4,7,10‐tetraacetic acid) are known to undergo relevant stereoisomeric equilibria in solution, which greatly modulate their chemical as well as their magnetic and optical properties. The subject is reviewed in terms of classical stereochemical description, with reference to conformational enthalpies. Yb is taken as the reference element because of its unique spectroscopic properties, namely, a small contact contribution to the paramagnetic shift and an intense near‐infrared electronic circular dichroism, endowed with an easily recognizable fine structure. The introduction and control of defined chiral centers on the scaffold of DOTA (see structure) imparts rigidity to the system and increases its structural homogeneity. Different locations of these chiral elements lead to different degrees of conformational prevalence.